The Study on the Customer's Use of Oriline Stock Trading With Reference to India : infoline Limited - Maran, (Gyan Management Journal, 2010)
The stock trading and broking is now a gay facing pressure from many number of directions like increased -etition, innovation in the technology, changing rules and regulations from the government side, changing . : :jmer preferences and many more. Development in the technology, and increased use of electronic media in had changed from paper stock trading system into on line stock trading. The present study is undertaken to the satisfaction level of customers in on line stock trading. The study was descriptive in nature describes :·,
Keywords: £-trading; Customer Satisfaction